2001
DOI: 10.1046/j.0962-1083.2001.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics, genome diversity and origin of modern leopard,Panthera pardus

Abstract: Leopards, Panthera pardus, are widely distributed across southern Asia and sub-Saharan Africa. The extent and phylogeographic patterns of molecular genetic diversity were addressed in a survey of 77 leopards from known geographical locales representing 13 of the 27 classical trinomial subspecies. Phylogenetic analysis of mitochondrial DNA sequences (727 bp of NADH5 and control region) and 25 polymorphic microsatellite loci revealed abundant diversity that could be partitioned into a minimum of nine discrete po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
280
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(303 citation statements)
references
References 40 publications
20
280
3
Order By: Relevance
“…These observations are restricted to some areas and may support the hypothesis that melanism can provide an adaptive advantage in certain ecological conditions [5,18]. At least four of the nine currently recognized leopard subspecies (based on [55]) are already cited in the literature as having confirmed records of melanistic animals: P. p. pardus, P. p. fusca, P. p. delacouri, and P. p. melas. However, the exact geographic range of this coloration phenotype has never been mapped in leopards in general, or in any of its subspecies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These observations are restricted to some areas and may support the hypothesis that melanism can provide an adaptive advantage in certain ecological conditions [5,18]. At least four of the nine currently recognized leopard subspecies (based on [55]) are already cited in the literature as having confirmed records of melanistic animals: P. p. pardus, P. p. fusca, P. p. delacouri, and P. p. melas. However, the exact geographic range of this coloration phenotype has never been mapped in leopards in general, or in any of its subspecies.…”
Section: Discussionsupporting
confidence: 58%
“…[55], significant geographic structure can be identified in leopards, indicating the existence of restricted historical gene flow among some portions of the range. This division formed the basis for currently recognized leopard subspecies, although in that study the authors noted that in some areas, such as African continent, Arabian Peninsula, Sri Lanka, and Java, the sampling was too sparse to identify clear-cut phylogeographic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample the Sinai female was much larger than the Arabian male leopard so they could belong to different subspecies, especially as the uniqueness of Arabian leopard was recently confirmed on a molecular genetic level (Uphyrkina et al, 2001). We have also found that the Arabian and Sinai leopards are totally separated from all the others in the Middle East (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Before this publication, we named the leopard in the Caucasus as Persian leopard P. p. saxicolor to indicate its connectedness with Iran (Khorozyan & Abramov, 2005). Some authors (Miththapala, 1992;Miththapala et al, 1996;Uphyrkina et al, 2001) claim that all leopards living in the Middle East, except the Arabian or South Arabian leopard P. p. nimr (Hemprich & Ehrenberg, 1833) whose distinctiveness was proved by molecular genetics, should be assigned a single name P. p. saxicolor as no significant geographical barriers allow for morphogenetic isolation of subspecies in this region. However, small sample size taken by these authors mostly from the zoos did not shed light on uncertain leopard systematics in the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with other recent pantherines (Figure 3) demonstrates that the degree of mitochondrial divergence is considerably greater than that found between well-defined subspecies in modern lion (P. leo) , leopard (P. pardus) (Uphyrkina et al, 2001), or tiger (P. tigris) (Luo et al, 2004). The estimated divergence time between P. leo and P. spelaea is also greater than that between the two newly recognised species of clouded leopard, Neofelis nebulosa and N. diardi, which has been estimated at 1.…”
Section: Dating the Divergence Between Spelaea And Leomentioning
confidence: 99%